Modelo de evaluación institucional, basado en el modelo de excelencia efqm para valorar la calidad de la gestión en la institución educativa n° 80313 "víctor raúl haya de la torre" de huayobamba - Salvatierra Moreno, Aurio Rolando (2016)
The purpose of investigation was proposing and applying the model of evaluation once the model of excellence was based on EFQM in the quality assessment of the step at the Educational Institution N 80313 Víctor Raúl Haya of the tower of the caserí, as well as of Huayobamba, Huranchal, Otuzco. The fact-finding design went from theoretic systemic character. He was worked up with a population show of 15 teachers, which were selected of mode not probabilistic in the sole discretion of the investigator. Right after applied instrument once the model of excellence was based on to sample's elements it was concluded that the model allows appraising the Educational Institution's various components definitively, just like the quality of the step in the habilitative components is deficient and satisfaction as the impact and results are equally deficient.